EVALUATION OF SOCIO-ECONOMIC RESULTSOF UKRAINIAN ECONOMY MANAGEMENT - TIURINA, NILA; KARVATSKA, NATALIIA; NAZARCHUK, TATIANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The paper was focused on researching the evolution and the reasons for the crisis in the economy of Ukraine for the period of independence. It was determined that the changes in the social and economic nature of the country’s development were followed by discrepancy in power and resources relations as well as in opposition between political forces and business elite. We analyzed the dynamics of changes in the main macroeconomic indicators in the development of the Ukrainian economy. The results showed that large-scale changes had different effects on the development of the national economy, which was characterized by long periods of crisis and short periods of extensive growth. Three main crises in the economical development have been characterized and the reasons for this were identified. We performed an assessment of the multiple indicators dynamics that characterise the outcomes of the economical governance. Specifically, the level of GDP per capita using purchasing power parity, the dynamics of export, import and balance of foreign trade as well as the dynamics of changes in the index of capital investment and the index of economic freedom. It has been established that the presence of effective structural changes in the economy of the country has caused the accumulation of internal and external economic imbalances. The results of the analysis of the rating assessment of the economy of Ukraine by international organizations showed consistently low positions of the country. We concluded that ineffective economic development became one of the main reasons for the deterioration of the social development of the country. Negative indicators of such development were a sharp decline in population, life expectancy, low wages and social security compared to other European countries.